Electrical and optical characterization of GaInP based heterostructures - Lui, Poh Yong. (2008)
This thesis presents the solid source molecular beam epitaxy (SSMBE) growth of Gao.52Ino.48P epitaxial layers, Gao.52Ino.48P/Ino.2Gao.8As/GaAs p-HEMT structures, and Gao 52lno.48P/GaAs single quantum well (SQW) on GaAs (100) substrate using the valved phosphorus cracker cell and valved arsenic cracker cell at various growth conditions. A study on defect properties, interface quality, and optical characterizations of the Gao.52Ino.48P/GaAs material system is included.